Biomedicine and traditional Chinese medicine: a fruitful scientific and cultural interaction - Mortara, Lorenzo; Coco, Grace; Pozzi, Cristina (Acta Biomedica Atenei Parmensis, 2022)
Over the years, the approach of traditional Chinese medicine has changed, as has the concept of the health status. Particularly in this article we will focus on the importance of some techniques that we can define millennial, as acupuncture. We will highlight the relationship between a millenary system and the principles of modernity, emphasizing the relevance of a technique that appears to be in line with the latest scientific research and numerous studies of effectiveness, proposing therapeutic integration as a usable way. We will see how acupuncture has an anti-inflammatory effect, and has a beneficial role in subjects suffering from allergic or autoimmune diseases, including an antihistamine action and downregulation of proinflammatory cytokines (e.g. IL-1β, IL-6 and TNF-α). In addition, acupuncture could also act as an immunomodulatory agent, involving the neuroimmune network, T helper and natural killer cells. Traditional Chinese medicine, acupuncture in particular, is widely used within Western health systems and there are many studies done regarding its efficacy in the clinical field. In addition to scientific validation, however, a comparison on a cultural level is also necessary. To build a constructive dialogue, indeed, it is necessary to deconstruct the preconceptions and prejudices concerning both biomedicine and traditional Chinese medicine. In fact, only through deconstruction we can understand that biomedicine and traditional Chinese medicine are both culturally connoted knowledge. In this article it will first be underlined how clinical observations can be better understood if we pay attention to analyzing the cultural context of the medical systems that here interact with each other. (www.actabiomedica.it)